Implementation of Green Hotel at New Sunari Lovina Beach Resort in Increasing Staff’s Environmental Concern - Adinata, Komang Ricky Wira; Widiastini, Ni Made Ary; Dewi, Luh Putu Triyanti Aristiana (International Journal of Green Tourism Research and Applications, 2024)
This research aims to analyze the implementation of the Green Hotel concept at New Sunari Lovina Beach Resort, Bali, and its impact on staff environmental awareness. Using qualitative descriptive methods, this research explores the practices implemented by efforts and eliminates factors influencing success and challenges in their implementation. This research shows that New Sunari Lovina Beach Resort has successfully integrated eco-friendly-friendly initiatives that increase environmental awareness among staff and optimize overall hotel operations. Practices such as energy efficiency, effective waste management, and ecological education for staff have been shown to play an essential role in promoting mortality. However, this research also identified challenges, including limited resources, the need for more comprehensive training, and difficulties in quantitatively measuring environmental impacts. Based on this analysis, the study recommends increasing investment in green technologies, developing more in-depth ecological training programs, and implementing more robust effectiveness measurement methods. The conclusion of this research is the commitment of New Sunari Lovina to maintaining tourism sustainability, including energy savings, effective waste management, and environmental education programs.